Chaos and strange attractors of the lorenz equations - Nurul Hidayah Salim, 1991-; Halijah Osman, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2014